Exploring online theological education at Hugenote Kollege - Potgieter, Annette; du Toit, André F. (Stellenbosch Theological Journal, 2023)
Theological education has come all the more under the scope as economic challenges and pressures of a changing society calls for renewed thinking on what theological education should entail. As Reformers, the quest is constantly realigning and adapting to communicate the gospel as effectively as possible. Within the broader purview of Reformed theological institutions in South Africa, Hugenote Kollege offers a unique BTh degree. The degree is fully online and follows an integrated curriculum with the main aim of educating lay ministers. This article explores the online BTh Hugenote Kollege as well as the benefit of online integrated education.